The Correlation among Learning Motivation, Parents’ Involvement and Speaking Achievement of the Fourth-Grade Pupils at Palembang Paramount School - Khoiriah, Olivia Nova; Simaibang, Baginda; Mulyadi, Mulyadi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This research was concerned with the inquiry on the correlation among learning motivation, parents’ involvement and speaking achievement of the fourth-grade pupil at Palembang Paramount School. The population of this study was 327, the sample was 38 taken by using purposive sampling. Data were collected by adopting a questionnaire for learning motivation and parents’ involvement, and test for speaking achievement. Data were analyzed by using r-Product Moment and Multiple Regression. Findings show that there were correlations among learning motivation, parents’ involvement, and speaking achievement. The data analysis shows that R_yx1x2 = 0.682 with r2 = 0.465 and the criteria of the sig-test was F_count(15.183) > F_table (3.270). therefore, the alternative hypothesis Ha was accepted while the null hypothesis Ho was rejected. Conclusions suggested that there were significant correlations among learning motivation, parents’ involvement and speaking achievement of the fourth-grade pupils at Palembang Paramount School.